Sustainable Winter-Tourism: the Project Snow-Cloud - Walter Klasz; Michael Bacher; Markus Ressl (Agathón)
This article describes an experimental and multidisciplinary project with the goal to provide an ecological alternative to the existing winter tourism in alpine regions. The project emerged from the fusion of new snowmaking technology, based on the principle of natural snowflake evolution and the spatial conception of wooden Cloud structures, which are placed in the local environments in a sense of functional land-art.